A novel insulin delivery system by β cells encapsulated in microcapsules - Luo, Zongjie; Dong, Yutong; Yu, Mengyu; Fu, Xiao; Qiu, Yudong; Sun, Xitai; Chu, Xuehui (Frontiers in Chemistry, 2023)
Introduction: Diabetes is a growing epidemic worldwide and requires effective clinical therapies. In recent years, β-cell transplantation has emerged as a promising treatment for diabetes, and an encapsulation approach has been proposed to ameliorate this treatment. Methods: Microfluidic technology had been used to generate microcapsules using a porous sodium alginate shell and a core containing β cells. The microcapsules were transplanted into diabetic mice and the therapeutic effect was measured. Results: Porous hydrogel shell allows exchange of small molecules of nutrients while protecting beta cells from immune rejection, while the core ensures high activity of the encapsulated cells. The glucose control effect of the microcapsules were more durable and better than conventional methods. Discussion: We believe that this system, which is composed of biocompatible porous hydrogel shell and enables highly activity of encapsulated β cells, can enhance therapeutic efficacy and has promising clinical applications.